Implementation of Policy Regulation of The Head of The National Land Agency Number 5 of 2012 Concerning Technical Instructions For The Implementation of Land Procurement - Abriyanto Nugroho; Adianto; Agus Priyanto (Faculty of Law, Merdeka University Surabaya, Indonesia, 2024)
That this research aims to analyze more deeply the implementation of the policy of the Head of the National Land Agency Regulation Number 5 of 2012 concerning Technical Instructions for Implementing Land Acquisition Case study of Land Acquisition for the Construction of the Pekanbaru-Bangkinang Toll Road, Riau Province. The research method in this legal research uses qualitative methods. The problem formulation used in this research is how to implement the policy of Regulation of the Head of the National Land Agency Number 5 of 2012 concerning Technical Instructions for Implementing Land Acquisition and what factors hinder the implementation of the policy of Regulation of the Head of the National Land Agency Number 5 of 2012 concerning Technical Instructions for Implementing Land Acquisition. That the results of this research found that the implementation of land acquisition for the construction of the Pekanbaru-Bangkinang toll road in Riau province was not optimal, that there were obstacles in the implementation of land acquisition for the construction of the toll road in the form of land disputes, the location being included in a forest area, and resistance from residents to the development. the toll road. The conclusion of this research is that it is best to review the regulations of the Head of the National Land Agency Number 5 of 2012 concerning Technical Instructions for the Implementation of Land Acquisition which function as a fulfillment of solving public problems in the land sector and filling legal gaps if necessary and that regarding the obstacles that In the field, assistance should be provided with related officials such as the prosecutor's office and police as well as the local district court to provide a sense of security and comfort for the committee and other stakeholders involved in the land acquisition process for the public interest.